أثر التعلم التنظيمي على أداء املنظمات دراسة حالة املؤسسة الوطنية للدهن – وحدة سوق أهراس - - سايغي ماجدة; بشرى حلاتة (My University, 2024)
The studyaims to highlight the impact of organizational Learning in its dimensions (individual learning, group Learning, organizational learning) on performance at the National Paint Company - Souk Ahras Unit. We adopted the descriptive analyticalapproach to highlight and analyze the concepts related to the study topic and to extrapolate the results. A questionnaire wasused to understand the opinions of the studysample, which consisted of 35 executives, control agents, and implementation agents at the National Paint Company - Souk Ahras Unit. The results wereanalyzedusing the SPSS statistical program, and the study results weretestedusing statisticalmethods. One of the most important findings of the studyis the strong impact of organizational learning on the performance of the National Paint Company - Souk Ahras Unit. تهدف الدراسة إلى إبراز أثر التعلم التنظيمي بأبعاده ( التعلم الفردي، التعلم الجماعي، التعلم التنظيمي ) على الأداء لدى المؤسسة الوطنية للدهن- وحدة سوق أهراس- ، وإعتمدنا على المنهج الوصفي التحليلي لإبراز المفاهيم المتعلقة بموضوع الدراسة وتحليلها وإستقراء النتائج، حيث تم استخدام أداةالإستبيان لمعرفة آراء عينة الدراسة المكونة من 35من الإطارات و أعوان التحكم وأعوان التنفيذ في المؤسسة الوطنية للدهن -وحدة سوق أهراس- ، وتم تحليل النتائج على البرنامج الإحصائي spss، وتم إختبار نتائج الدراسة بإستعمال الأساليب الاحصائية، ومن أهم النتائج التي توصلت لها الدراسة وجود أثر قوي للتعلم التنظيمي على أداء المؤسسة الوطنية للدهن- وحدة سوق أهراس- . L’étude vise à mettre en évidence l’impact de l’apprentissage organisationnel dans ses dimensions (apprentissage individuel, apprentissage collectif, apprentissage organisationnel) sur la performance à l’Entreprise Nationale de Peinture – Unité Souk Ahras. Nous avons adopté l'approche analytique descriptive pour mettre en évidence et analyser les concepts liés au sujet d'étude et extrapoler les résultats. Un questionnaire a été utilisé pour comprendre les opinions de l'échantillon de l'étude, composé de 35 cadres, agents de contrôle et agents d'exécution de la Société Nationale de Peinture - Unité Souk Ahras. Les résultats ont été analysés à l'aide du programme statistique SPSS et les résultats de l'étude ont été testés à l'aide de méthodes statistiques. L’une des conclusions les plus importantes de l’étude est le fort impact de l’apprentissage organisationnel sur la performance de l’Entreprise Nationale de Peinture – Unité Souk Ahras.
Keywords: apprentissage organisationnel; performance organisationnelle; The National Paint Company - Souk Ahras Unit.; الكلمات المفتاحية: التعلم التنظيمي، أداء المنظمات،المؤسسة الوطنية للدهن-وحدة سوق أهراس.; Mots-clés : apprentissage organisationnel; The National Paint Company - Unité Souk Ahras